Estudo da aplicação de ore sorting para minério silicatado de zinco - Gilvan de Souza Amorim Júnior (2022)
In Brazil, the main mining plants of Zn, in activity, are in the cities of Paracatu and Vazante, both in Minas Gerais. Zn contents in the ROM (Run of Mine) of the Vazante mine have been reducing over the years, in 2006 the feed content at the plant was 15.7%, to 11.34% in 2015, and is estimated to be 10.75% in 2021. To compensate for the production by reducing the Zn contained in the plant feed, the company has been working in many ways, such as: increasing the mass feed at the plant, flotation optimization, and, also the implementation of an ore sorting plant. Based on the need to adjust the ore sorting plants to seek the maximum of their capacity and recovery, this work aims to carry out studies on the ore sorting plant already existing in the company, as well as to investigate and analyze optimal parameters for new plants. The study of the curves of recoveries, enrichment, and tailings contents as a function of the feed content, allowed to observe a range of opportunities for simulation of the ore sorting, for this work it was decided to work with metallurgical recovery and tailings contents in the range of 35 to 10 mm seeking to approach the operational reality of the equipment, where there is a search for lower levels of tailings content thus varying the ejection and consequently the mass recovery. Studies to use the simulator in the mass balance of the plant allowed the application of several operating scenarios, as well as to perceive the impact of the ore sorting operation on the production of ZnC and ROM feed in the plant. The equipment can be used for various applications, such as milling cost reduction, flotation, dry stacking, and other costs tied to the feed of the plant, without impacting the production of ZnC, increasing ZnC production keeping ROM contents and the capacity of the plant, keep ZnC production with low ROM contents without changing the processing capacity of the plant.